Does Innovative Financing Increase the Firm Performance? An Empirical Investigation of Indian Manufacturing Firms - Vunyale, Narender; Raja, Nemi; Krishnankutty, Raveesh (Scientific Research, 2016)
The firms mobilizing resources using innovative debt from market reduce dependence on the traditional banking and financial institutions. The firms raising resources by directly approaching public have some incentive to do so, i.e., innovative firms will be able to better plan commitments of future cash outflow and inflow, increase the borrowing capacity, save taxes, etc. to create higher value to the shareholders. In this paper we have made an attempt to test whether such innovative firms’ performance is higher than other firms. We also tried to understand if more variety of instruments helped create better value of share in the market for such firms.
Keywords: Firms’ Performance; Innovative Firms’; Innovative Financing; Innovative Debt; Value of Firm; Indian Manufacturing Firm